Screening of biotechnical parameters for production of bovine inter-subspecies embryonic chimeras by the aggregation of tetraploid Bos indicus and diploid crossbred Bos taurus embryos - Razza, Eduardo M.; Satrapa, Rafael A.; Emanuelli, Isabele P.; Barros, Ciro M.; Nogueira, Marcelo F.G. (Elsevier, 2016)
The aggregation of a tetraploid zebu embryo (Bos indicus, a thermotolerant breed) with a diploid taurine embryo (Bos taurus, a thermosensitive breed) should create a complete taurine fetus, whose extra-embryonic components, e.g., the chorion, is derived mainly from the zebu embryo. These zebu-derived extra-embryonic components may interact positively with the taurine embryo/fetus during pregnancy in a tropical environment. We tested different parameters for the production of tetraploid Nelore (Bos indicus) embryos to be combined via aggregation with crossbred Bos taurus (diploid) embryos in order to produce viable chimeric blastocysts. Bovine (Bos indicus or crossbred Bos taurus) embryos were produced in vitro according to standard procedures. Two-cell Bos indicus embryos were submitted to electrofusion with varying numbers of pulses (1 or 2), voltages (0.4, 0.5, 0.75, 1.0, 1.4 and 5.0 kV/cm) and time (20, 25, 50 and 60 μs) to produce tetraploid embryos. Electrofused embryos were cultured with crossbred non-fused embryos to form chimeras that developed until the blastocyst stage. The best fusion parameter was 0.75 kV/cm for 60 μs. Four chimeric blastocysts (tetraploid Nelore with diploid crossbred Holstein) were formed after 31 attempts in 4 replicates (13%). We established an optimal procedure for the production of tetraploid Bos indicus (4n) embryos and embryonic chimeras by aggregation of crossbred Bos taurus (2n) with Bos indicus (4n) embryos. This technique would be valid in applied research, by producing exclusively taurine calves, but with placental elements from the Bos indicus breed, following transfer of these chimeras into recipient cows.
Keywords: Bovine; Chimerism; Embryo; Tetraploid